2021
DOI: 10.3390/cells10061479
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Irisin in Cancer Disease

Abstract: Irisin (Ir) is an adipomyokine that is involved in the regulation of metabolic processes. It also influences processes related to inflammation, including cancer. Initially, Ir was considered a hormone secreted by skeletal muscles in response to physical exercise. Further studies showed that Ir is also present in other healthy tissues, organs, and plasma. It influences the change in phenotype of white adipose tissue (WAT) into brown adipose tissue (BAT). It increases mitochondrial biogenesis and affects the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…Irisin is released as a result of post-translational modifications of the FNDC5 prohormone, encoded by the FNDC5 gene. The peptide composed of 112 amino acids is the result of cleavage and glycosylation of the extracellular domain of the prohormone [ 11 , 12 ]. FNDC5 is an N-glycan with two potential glycosylation sites (Asn36 and Asn81) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irisin is released as a result of post-translational modifications of the FNDC5 prohormone, encoded by the FNDC5 gene. The peptide composed of 112 amino acids is the result of cleavage and glycosylation of the extracellular domain of the prohormone [ 11 , 12 ]. FNDC5 is an N-glycan with two potential glycosylation sites (Asn36 and Asn81) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that FNDC5 protects cells from oxidative damage in myocardial inflammation and neurological diseases ( 20 , 21 ) and reduces the production of ROS, inhibiting the occurrence of ferroptosis in cells ( 22 ). As the role of FNDC5 has also been gradually revealed in tumors ( 23 , 24 ) and in the progression of HCC, FNDC5 has been suggested to play a role in promoting the proliferation of cancer cells. In our previous study, we found that the expression of FNDC5 was higher in cancer than in normal tissues ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have also been conducted to investigate irisin’s role in other cancers [ 73 , 74 ]. It was found that an increase in the level of irisin leads to decreased proliferation, viability, and invasiveness in a lung cancer cell by inhibiting EMT mediated by the PI3K/Akt pathway [ 32 ].…”
Section: The Role Of Irisin In Human Pathophysiologymentioning
confidence: 99%
“…It was revealed that irisin could reverse IL-6-induced EMT by inhibiting the STAT3 pathway in osteosarcoma [ 74 ]. Irisin has been found to affect the expression of Snail (transcription factor), which is involved in EMT, and inhibits the transcription of the gene encoding E-cadherin, a characteristic of epithelial-derived cells [ 73 ]. A report showed that the level of irisin significantly increases in patients with renal tumors, hence suggesting that irisin can be used as a biomarker for renal cancer diagnosis [ 75 ].…”
Section: The Role Of Irisin In Human Pathophysiologymentioning
confidence: 99%